"I Kick It to Both, but not in the Street": Behaviorally Bisexual Latino Men, Gender, and the Sexual Geography of New York City Metropolitan Area. (April 2018) - Muñoz-Laboy, Miguel; Severson, Nicolette; Garcia, Jonathan; Parker, Richard G.; Wilson, Patrick
This article examines how behaviorally bisexual Latino men negotiate, modify, and perform their gender within distinct social spheres. An analysis was made of 148 sexual histories of Latino men aged eighteen to sixty, from a cross-sectional, multiyear study in New York City. A familial sphere of gender norm negotiation was sharply contrasted with conformity to elements of dominant or hegemonic forms of masculinity performed on streets of neighborhoods of residence. Rather than a strict dichotomy, our participants revealed a spectrum of masculine representations that worked to manage the risk of nonheterosexual stigma. Participants adopted variable configurations of masculinity to reconcile the plurality of their sexual practices, distinct social spaces, and socially sanctioned gender norms.